RANCANG BANGUN MESIN WRAPING SEPATU OTOMATIS MENGGUNAKAN MIKROKONTROLLER - Andi Syofian; Yultrisna Yultrisna (Ensiklopedia of Journal, 2026)
In industrial work, it is not always the place where the ongoing work is always in a dirty state, sometimes there are several industrial companies that demand cleanliness in production activities or in work activities both cleaning the surrounding environment and cleaning of the workers themselves. The automatic shoe wrapping machine is here to meet these needs where this machine has a function to cover the surface of the shoe sole to the top by using plastic. Because shoes are a sure source it can cause the environment around the work to become dirty, especially on the floor surface and it can also happen on machines that operate using feet. Keywords: wrapping machine, Microcontroller, Fan, Heating Element, Ultrasonic Sensor